Antihypertension Profile During Pregnancy at a Private Hospital in Surabaya - Wiputri, Oktaviany Irma; Rahma, Iftakhur; Samlan, Karima (Borneo Journal of Pharmacy, 2025)
Hypertension during pregnancy, a significant obstetric complication, can lead to severe consequences such as preeclampsia. This study aimed to determine the pattern of antihypertensive medication use, including drug type, route of administration, dosage, and frequency, as well as investigate the relationship between clinical data, including blood pressure and proteinuria, and the use of single or combination antihypertensive therapy in pregnant women with hypertension. A retrospective observational study was conducted on 108 pregnant women with hypertension admitted to the inpatient unit of a private hospital in Surabaya, Indonesia. Data on patient demographics, comorbidities, antihypertensive medications, blood pressure, and proteinuria levels were collected and analyzed. The majority (79.65%) of patients were aged between 20 and 35 years. Common comorbidities included obesity (62.50%), pre-existing hypertension (18.75%), and a history of preeclampsia in previous pregnancies (6.25%). Nifedipine (73.26%) was the most frequently used single antihypertensive medication, followed by methyldopa (23.26%). Combination therapy, primarily nifedipine and methyldopa (92.31%), was commonly employed. Most patients (97.35%) achieved blood pressure control, and 47.79% showed improvement in proteinuria levels. Nifedipine and the combination of nifedipine and methyldopa were the most frequently used antihypertensive medications in this cohort. Most patients achieved blood pressure control, indicating effective management of hypertension during pregnancy. Further studies are warranted to investigate the long-term outcomes and optimize antihypertensive therapy strategies in this population.